Науково-методичні аспекти прогнозування витрат і планування сталого розвитку агропідприємства - Кернасюк, Ю. В.; Kernasyuk, Yu. (ЦНТУ, 2018)
В статті розглянуто питання організації забезпечення прогнозування витрат і планування сталого розвитку сільськогосподарського підприємства. Здійснено аналіз сучасного економічного стану розвитку аграрних підприємств на регіональному, зональному і загальнодержавному рівні. Узагальнено теоретичні аспекти визначення дефініції «сталий розвиток» для аграрного підприємства. Науково обґрунтовано методичні підходи прогнозування витрат і планування сталого розвитку аграрного підприємства з врахуванням впливу ринкового середовища, погодно-кліматичних умов та інших факторів. В статье рассмотрены вопросы организации обеспечения прогнозирования расходов и планирования устойчивого развития сельскохозяйственного предприятия. Осуществлён анализ современного экономического состояния развития аграрных предприятий на региональном, зональном и общегосударственном уровне. Обобщены теоретические аспекты определения дефиниции «устойчивое развитие» для аграрного предприятия. Научно обоснованы методические подходы прогнозирования расходов и планирования устойчивого развития аграрного предприятия с учётом влияния рыночной среды, погодно-климатических условий и других факторов. The purpose of the article is the generalization and development of scientific and methodical approaches to forecasting expenditures in combination with planning for sustainable development of an agricultural enterprise based on the use of economic modeling methods, system analysis and intelligent computer technologies. In the modern economy, one of the important aspects of the competitive functioning of agribusiness enterprises on the principles of sustainable development is the effective management of their financial and material resources. Now it is difficult and problematic to achieve high performance results in the management of enterprises without a comprehensive use of economic modeling methods, system analysis and intelligent computer technologies that significantly expand the existing information and analytical support for forecasting costs and the level of profitability of production activities. The article deals with the organization of ensuring the forecasting of expenditures and planning the sustainable development of an agricultural enterprise. The analysis of the current economic state of the development of agrarian enterprises at the regional, zonal and national levels is carried out. The theoretical aspects of defining the definition of "sustainable development" for an agrarian enterprise are generalized. The methodical approaches to forecasting costs and planning sustainable development of an agricultural enterprise, taking into account the influence of the market environment and other factors were substantiated scientifically. It was suggested to use the tool in the Excel spreadsheet editor, which is called the "Scenario Manager" to automate the calculation of the cost forecast. The scenario approach of the forecast of costs based on 5 variants is grounded. An economic model of cost forecasting based on the example of soybean production is developed. The advantage of this is the ability to provide management with a convenient tool for substantiating and making informed decisions taking into account the influence of the market environment, weather and climate, environmental conditions and other factors. The forecasting model allows to take into account a significant number of factors of influence and trends in the development of super complex systems, including agriculture, and also to ensure a higher level of its reliability.
Научно-методические аспекты прогнозирования затрат и планирования устойчивого развития агропредприятия
Scientific and Methodical Aspects of Cost Forecasting and Sustainable Development Planning for Agro-enterprises
Keywords: прогнозування; витрати; сталий розвиток; модель; планування; підприємство; прогнозирование; расходы; устойчивое развитие; планирование; предприятие; forecasting; costs; sustainable development; model; planning; enterprise